HUMAN RESOURCES TRAINING AND DEVELOPMENT: A SYSTEMATIC LITERATURE REVIEW AND BIBLIOMETRIC ANALYSIS - Putri, Rifqa Faulia; Sopiah (Transpublika Publisher, 2022)
A company to continue to grow, it must be supported by human resources who have good competence and are also reliable. Therefore, human resources in companies must pay attention to their needs in increasing their abilities and skills through training and development. This study aims to examine more broadly about the training and development of human resources. The literature in this study used three databases Taylor & Francis, Sage Journals and Emerald Insight to filter articles published in 2017-2022 with bibliometric studies and PRISMA (Preferred Reporting Items for Systematic Reviews and Metaanalysis) method to gain 30 articles. The results describe the analysis of 132 authors based on co-authorship, and new keywords from co-occurrence data such as training need assessment, skill development, work engagement, training model and higher education. In addition, there are top 10 citations revealed. This research is expected to be a reference for next research on HR training and development.